Thoreau and the American Indians. - Sayre, Robert F. (Princeton legacy library., 2014)
Thoreau turned toward Indians in his writing as well as in his life, and this book traces the long and arduous process by which his ideas about Indians evolved from savagist stereotypes to attitudes of greater originality. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The g.